2020
DOI: 10.1038/s41598-020-72934-3
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine level, body mass index and clinical correlates in Chinese Han patients with schizophrenia

Abstract: Obesity is common comorbidity in patients with schizophrenia. Previous studies have reported that homocysteine (Hcy) is increased in schizophrenia. However, no study has reported the association between BMI and Hcy levels in schizophrenia. This cross-sectional naturalistic study aimed to evaluate the relationship between BMI, Hcy and clinical symptoms in Chinese Han patients with chronic schizophrenia. Clinical and anthropometric data as well as plasma Hcy level and glycolipid parameters were collected. Psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
5
12
0
1
Order By: Relevance
“…The inconsistent results for this association are unclear. One possible reason may be due to the differences in subjects who had suffered from different diseases, BMIs, regions of residence, races, dietary habits, genetic backgrounds or courses of illness [21][22][23][24] ; for example, the subjects in the present study were inpatients, and most had suffered from schizophrenia for a long time.…”
Section: Discussionmentioning
confidence: 92%
“…The inconsistent results for this association are unclear. One possible reason may be due to the differences in subjects who had suffered from different diseases, BMIs, regions of residence, races, dietary habits, genetic backgrounds or courses of illness [21][22][23][24] ; for example, the subjects in the present study were inpatients, and most had suffered from schizophrenia for a long time.…”
Section: Discussionmentioning
confidence: 92%
“…The inconsistent results for this association are unclear. One possible reason may be due to the differences in subjects who had suffered from different diseases, BMIs, regions of residence, races, dietary habits, genetic backgrounds or courses of illness 19 22 ; for example, the subjects in the present study were inpatients, and most had suffered from schizophrenia for a long time.…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, folic acid (vitamin B9), piroxidine (vitamin B6), and cobalamine (vitamin B12) deficiencies have been reported common in SZ patients. Total plasma homocysteine (Hcy) level is considered as a sensitive measure of these deficiencies and elevated Hcy levels have been widely associated with the etiology of numerous health impairments, especially cardiovascular diseases and several mental health disorders such as Alzheimer's disease and SZ ( 164 ) and some studies have reported a positive correlation between Hcy levels and SZ illness severity ( 165 ).…”
Section: Gut Microbiota Diet and Schizophreniamentioning
confidence: 99%